Controlled synthesis of bimetallic Pd–Rh nanoframes and nanoboxes with high catalytic performances1. Issue 21 (7th June 2015) - Ye, Wei; Kou, Shufang; Guo, Xia; Xie, Fang; Sun, Hongyan; Lu, Haotian; Yang, Jian
<x xml:space="preserve">Abstract</x> Bimetallic nanoframes and nanoboxes of Pd–Rh are synthesized by selective removal of Pd cores from different Pd–Rh nanocubes prepared by a hydrothermal reaction of PdCl2, RhCl3 and HCHO.